Influence Application Time Management on Employee Performance at the Department of Trade and Industry Regency Gowa - Sitti Nur Fatimah; Moh. Aris Pasigai; M. Hidayat (Income Journal Of Economics Development, 2024)
Type of presearch is quantitative research with the aim of finding out the effect of implementing time management on employee performance at the Gowa Regency Trade and Industry Service. The sample in this study amounted to 40 people. The type of data used in this research is quantitative data obtained from distributed questionnaires and is related to the problem being studied. Data collection was carried out by observation and distribution of questionnaires. The data sources used in data collection are primary data and secondary data. Data analysis uses Simple Linear Regression and is processed using the Statistical Package For The Social Science (SPSS) version 23 application . The results of the research show the effect of implementing time management on employee performance at the Gowa Regency Trade and Industry Service which has been discussed in the previous chapter, so the author draws conclusions The important thing is that the application of time management has a positive and significant effect on employee performance. The contribution of the independent variable to the dependent variable is R 2 , while the rest is influenced by factors or independent variables with a significance value of 0.05 and the t-calculated value is greater than the t-table ( 3,604 > 1,685) which is able to contribute to employee performance variables.